Emissions salt and gas at underground dissolution - V P Malyukov (RUDN Journal of Engineering Research, 2012)
The experimental investigation of the subsurface dissolution of rock salt from the salt and gas emissions, as well as determine themass-transfer coefficient that characterizes morphogenesis and speed of construction of underground workings to reserve tanks of hydrocarbons.